Respuesta :

Answer:

b

Step-by-step explanation:

[tex]\left[\begin{array}{ccc}-1&-3&2\\2&5&-1\\-4&-5&-4\end{array}\right] *\left[\begin{array}{ccc}3&3&5\\2&-5&2\\-4&-1&1\end{array}\right] \\\\\\[/tex]

c11 = (-1) *3 + (-3)*2 + 2*(-4) = -3 - 6 - 8 = -17

C12 = (-1)*3 + (-3)*(-5) + 2*(-1) = -3 + 15 - 2 = 10

C13 = (-1)*5 + (-3) *2 + 2*1 = -5 - 6 +2 = -9

C21 =  2*3 + 5*2 + (-1)*(-4) = 6 +10 + 4 = 20

C22 =  2*3 + 5*(-5) + (-1)*(-1) = 6 - 25 + 1 = -18

C23 =  2*5 + 5 *2+ (-1)*1    = 10 + 10 -1 = 19

C31 = (-4)*3 + (- 5)*2  + (-4)*(-4)  = -12 - 10 +16 = -6

C32 = (-4)*(3) + (- 5)*(-5)  + (-4)*(-1) = -12 + 25 + 4 = 17

C33 = (-4)*5 + (- 5)*2  + (-4)*1 = -20 - 10 - 4 = -34

[tex]AB = \left[\begin{array}{ccc}-17&10&-9\\20&-18&19\\-6&17&-34\end{array}\right][/tex]